1989
DOI: 10.1152/ajpregu.1989.256.1.r248
|View full text |Cite
|
Sign up to set email alerts
|

Release of hypothalamic cholecystokinin in cats: effects of nutrient and volume loading

Abstract: Systemic cholecystokinin (CCK) suppresses food intake in various species and has therefore been proposed to act as a satiety factor. Because CCK is also present in the hypothalamus and furthermore meets neurotransmitter criteria, the hypothesis was tested whether CCK participates in the transmission of satiety messages at the lateral hypothalamic (LH) level. The results of this study demonstrate that in halothane-anesthetized cats, neurons located in the LH will indeed release CCK-like material after a carbohy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0
1

Year Published

1990
1990
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 0 publications
2
17
0
1
Order By: Relevance
“…More recent experiments have shown that CCK-LI is released in the lateral hypothalamus during food intake (4,16,17). In the present study, we found that the concentration of CCK-LI in the CSF of male rats decreased in response to 48 h of food deprivation and was restored after 1 h of food intake.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…More recent experiments have shown that CCK-LI is released in the lateral hypothalamus during food intake (4,16,17). In the present study, we found that the concentration of CCK-LI in the CSF of male rats decreased in response to 48 h of food deprivation and was restored after 1 h of food intake.…”
Section: Discussionsupporting
confidence: 67%
“…We suggested that peripheral CCK-8 may exert a triggering effect on the central neural pathways which control food intake (2). In fact, CCK may serve as a neurotransmitter in these pathways (2)(3)(4). Thus, sensory information from the gastrointestinal tract is relayed via gastric vagal afferents to the parvocellular division of the nucleus of the holitary tract (5,6) and further to the parabrachial nucleus in the pons (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since these were dose response studies, it obviously cannot be determined whether these regions actually encounter similar concentrations of CCK as the result of changes in appetite or satiety. In cats, 119 CCK can be released from neurons in the lateral hypothalamus in response to gastric infusion of nutrients as well as to volumetric distension by water alone. Peripheral CCK was demonstrated not to be involved using a set of control cats infused IV with exogenous CCK.…”
Section: B Central and Peripheral Regulatory Factorsmentioning
confidence: 99%
“…The mechanism is believed to include gastric distension and possibly other signals from the upper intestinal tract mediated through the vagus nerve (Lorenz, 1983). Gastric loads of nutrient or nonnutrient solutions stimulate the release of CCK in the lateral hypothalamus of anesthetized adult cats (Schick, Yaksh, Roddy, & Go, 1989). Perhaps central cholecystokinin is part of the gastric distension mechanism, a mechanism suspected to be involved in the control of intake by rats of all ages, regardless of the mode of ingestion (Lorenz, 1992).…”
mentioning
confidence: 99%